Potensi Implementasi STEAM (Science, Technology, Engineering, Art and Mathematic) berorientasi ESD (Education for Sustainable Development) dalam Pembelajaran Fluida - Widarti, Rezki; Roshayanti, Fenny (UPEJ Unnes Physics Education Journal, 2021)
This study aims to analyze the potential implementation of STEAM (Science, Technology, Engineering, Art and Mathematics) oriented to ESD (Education for Sustainable Development) in fluid learning. This research is a type of qualitative descriptive research. Physics learning at Madrasah Aliyah tends to be theoretical and has not optimized the surrounding objects as learning resources. The researcher will describe the potential for implementing ESD-oriented STEAM in fluid learning carried out by physics teachers at Madrasah Aliyah, Demak Regency. Data collection techniques used observations, interviews and questionnaires about the implementation of ESD-oriented STEAM in fluid learning. The results showed that 90% of teachers were familiar with the STEAM learning approach, 52% of teachers had implemented STEAM in fluid learning, 62% of teachers had recognized the potential of ESD, 86% of teachers had linked fluid material to environmental issues. The learning process is carried out using a project base learning model. The conclusion is that the potential for implementing ESD-oriented STEAM in fluid learning is able to overcome the problem of students' learning difficulties which is carried out through experiments by utilizing waste or unused materials.